Bringing Literacy Into Bilingual Science: Using Cognitive Discourse Functions to Support Reading and Writing in English as a Foreign Language Classrooms - Hung, Yueh‐Nu (The Reading teacher, 2025)
ABSTRACT In bilingual elementary classrooms where English is taught as a foreign language, science lessons often prioritize spoken interaction, while reading and writing receive less emphasis. This article explores how Cognitive Discourse Functions (CDFs)—such as defining, explaining, hypothesizing, and evaluating—can support disciplinary and interdisciplinary literacy development by integrating English language use into content learning. Drawing on three classroom vignettes from public schools in Taiwan, the article illustrates how science teachers designed lessons that help students read scientific texts, write lab reports, and engage in structured discussions—all in English. Practical guidelines are provided to help K–6 educators incorporate reading and writing into bilingual science instruction, with an emphasis on multimodal scaffolding and English academic language development. The paper highlights how CDFs can serve as a bridge between content and language learning, helping students deepen their understanding of scientific concepts while also building the literacy skills needed to think and communicate like scientists in English.